Well-known Mark Overseas Legal Protection and Local Brands in Trademark Rights Violations - andaniswari, okky (Faculty of Law, Universitas Negeri Semarang, 2019)
Brand rights relating to the Law Number 20 of 2016 concerning Trademark Rights and Geographical Indications, it can be concluded that those who are entitled to legal protection for trademark disputes are the users and the first registrant of the brand used. Brand is one form of Intellectual Property Rights (IPR) that is used to recognize and differentiate products or services. However, brands are very vulnerable to being copied by irresponsible parties. The imitation of the brand has an impact on material and non-material losses. The perpetrators of brand rights violations, especially for brands that are at a well-known level, brand rights holders can make legal safeguards regulated in the Law Number 15 of 2001 concerning Trademarks which are changed to the Law Number 20 of 2016 concerning Trademarks and Indications Geographical. One of the legal efforts applied is through arbitration or alternative dispute resolution. The step resulted in a decision that was the termination of all actions related to the use of the imitated brand.